2011
DOI: 10.1097/mpg.0b013e3182145511
|View full text |Cite
|
Sign up to set email alerts
|

Use of Deamidated Gliadin Peptide Antibodies to Monitor Diet Compliance in Childhood Celiac Disease

Abstract: Both a-DGPs showed higher sensitivity than anti-tTG IgA and AGA IgA in monitoring compliance with GFD, but a-DGP IgA+G seemed to perform better. a-DGPs did not outperform anti-tTG IgA for CD screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 33 publications
3
33
0
1
Order By: Relevance
“…Our findings that performance of tTG is extremely good, but that sensitivity can be increased if tTG and DGP are combined (positive tTG or DGP required) are in concordance with earlier studies (7,9,11,15); however, the relatively poor test performance of DGP found in our study, with a large proportion of false-positives has only been described once before in a study of 116 children with high risk for CD (16). In that study, as well as in ours, serology samples were analyzed prospectively in standard medical care as opposed to all of the earlier studies, which may be part of the explanation for the dramatic difference in results regarding DGP specificity.…”
Section: Discussionsupporting
confidence: 94%
“…Our findings that performance of tTG is extremely good, but that sensitivity can be increased if tTG and DGP are combined (positive tTG or DGP required) are in concordance with earlier studies (7,9,11,15); however, the relatively poor test performance of DGP found in our study, with a large proportion of false-positives has only been described once before in a study of 116 children with high risk for CD (16). In that study, as well as in ours, serology samples were analyzed prospectively in standard medical care as opposed to all of the earlier studies, which may be part of the explanation for the dramatic difference in results regarding DGP specificity.…”
Section: Discussionsupporting
confidence: 94%
“…80 To further support the use of DGP in young children, Monzani, et al showed that DGP IgA and IgG had sensitivity levels of 100% in children younger than three years. 81 Similar results were also recently obtained by Mubarak et al 82 in an investigation in 212 children with suspected CD: when the analysis was restricted to the 41 children below 2 years of age, the DGP-IgG had a diagnostic accuracy of 100%.…”
Section: Diagnosis In Childrensupporting
confidence: 82%
“…A strong correlation between the anti-tTG titer and duodenal histological changes has been demonstrated [26–28]. Moreover, the tests can be used to monitor the response and compliance to a gluten-free diet (GFD) among celiac disease patients [29]. Although a duodenal biopsy remains the gold standard diagnostic test, pediatric endoscopy is not readily available in most hospitals and is an invasive procedure.…”
Section: Introductionmentioning
confidence: 99%